PP081 Relation Between Pain And Treatment/Activity Based On Mobile App Data. (12th January 2018) - Iwasaki, Kosuke; Inoue, Hideki; Hiki, Takeru; Takeshima, Tomomi
Abstract : INTRODUCTION: Recently, a number of mobile apps to record symptoms and medication by patients themselves have been developed. These apps are expected to improve the patients' symptoms through self-management, and to enable a smooth decision making through effective communication between doctors and patients. "Itami Renrakucho" (Pain Diary, Welby Inc.) is one of these apps that records body pain, medication, physical conditions, and activity in life. We examined the relationship between pain and medication/activity based on its data. METHODS: Data between 25 December 2015 and 9 December 2016 were used. Medication and degree of pain (0-10, low < high) were recorded at morning, daytime, evening, and bedtime. Of ninteen activities, up to three were recorded about whether they could or could not do them. We compared the degree of pain among different frequency/timing of medication, or activities that they could or could not do. RESULTS: Data included 708 individuals. Among 561 individuals who answered about pain, the mean (Standard Deviation, SD) degree was 5.0 (2.3). The mean degree in individuals taking 0, 1, 2, 3, and 4 times medication a day were 4.6, 5.0, 5.4, 5.5, and 6.2, respectively. Regarding medication timing and degree of pain in two consecutive time points (t0, t1 ), regression towards the mean occurred for individuals without medication in both time points. The degree changed more for individuals taking medicine only at t0, but not for those taking at both time points. Weaker pain was reported when they could do hanging laundry and rising early than when they could not, but they could do shopping, strolling and light exercise even having stronger pain. CONCLUSIONS: We showed a tendency of relationship between pain and medication/activity based on the data from the app. More data and connecting to claims will help us to show characteristics of patients and diseases, select a treatment, and evaluate a medicine.